Mitigating Human Rights Violations: A Critical Examination of Excessive Overtime Practices in the Workplace - Isnaini, Nurun; Rusdiana, Shelvi; Tan, Winsherly (Journal of Judicial Review, 2024)
In the pursuit of project goals, expediting implementation time is crucial. This study delves into the prevalent use of overtime work as a means to accelerate projects, particularly in industries striving to meet production targets. Despite government regulations stipulating permissible durations for overtime, numerous companies exceed these limits, leading to labor-related violations that infringe upon human rights. This research, employing a normative doctrinal approach, explores the impact of exceeding specified overtime limits on human rights. Recognizing human rights as fundamental and universal, the study advocates for their impartial application to all workers, irrespective of their employment status. Addressing violations through comprehensive discussions and interventions is imperative to foster a workplace that upholds the principles of non-discrimination and respects fundamental human rights.